2012
DOI: 10.1007/s12038-012-9282-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Raloxifene in reversing osteoarthritis-like alterations in rat chondrocytes: An in vitro model study

Abstract: The aim of this study was to investigate the effects of Raloxifene (Ral) on degeneration-related changes in osteoarthritis (OA)-like chondrocytes using two- and three-dimensional models. Five-azacytidine (Aza-C) was used to induce OA-like alterations in rat articular chondrocytes and the model was verified at molecular and macrolevels. Chondrocytes were treated with Ral (1, 5 and 10 mu M) for 10 days. Caspase-3 activity, gene expressions of aggrecan, collagen II, alkaline phosphatase (ALP), collagen X, matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Additionally, the microspheres showed a significant decrease in average particle size, which might have contributed to the enhancement of release by increasing the surface/volume ratio of the drug delivery system. Although in vitro release amounts of Ral were very small (∼1 μM), this dose is expected to be effective in cartilage regeneration as reported in our previous study . Hydrophobic drugs such as Ral are released with a slow rate from polymeric matrices.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Additionally, the microspheres showed a significant decrease in average particle size, which might have contributed to the enhancement of release by increasing the surface/volume ratio of the drug delivery system. Although in vitro release amounts of Ral were very small (∼1 μM), this dose is expected to be effective in cartilage regeneration as reported in our previous study . Hydrophobic drugs such as Ral are released with a slow rate from polymeric matrices.…”
Section: Resultsmentioning
confidence: 53%
“…Although in vitro release amounts of Ral were very small (∼1 :M), this dose is expected to be effective in cartilage regeneration as reported in our previous study. 28 Hydrophobic drugs such as Ral are released with a slow rate from polymeric matrices. Initially, we aimed to enhance Ral release by using coloading with a more hydrophilic drug that would initially open the pores for water penetration into the system.…”
Section: Release Studiesmentioning
confidence: 99%
“…The other therapies were also tried in the management [24,25]such as lubricin, raloxifen, antioxidants, cathepsins, NGF antibodies, strontium ranelate and various growth factors. Because of the heterogeneity in study design, data collection and data presentation, I did not pool summary data in a metaanalysis.…”
Section: Resultsmentioning
confidence: 99%
“…The consistent effect of SERMs in vivo indicates a protective effect on chondrocytes. Kavas et al [ 53 ] reported that 1 μM of raloxifene reduced expression of OA-related genes, apoptosis, and extracellular matrix-degrading enzymes, and increased extracellular matrix deposition and improved mechanical properties in rat articular chondrocytes with OA-like degeneration. However, these effects were reversed with increased dose, demonstrating that low-dose raloxifene has the potential to cease or decrease cartilage degeneration in OA.…”
Section: Serm Treatment: Consistent Evidencementioning
confidence: 99%